Serum 25(OH)D Level and Parathyroid Hormone in Chinese Adult Population: A Cross-Sectional Study in Guiyang Urban Community from Southeast of China - Zhang Qiao; Shi Li-xing; Peng Nian-chun; Xu Shu-jing; Zhang Miao; Li Hong; Zhuang Hui-jun; Gong Ming-xian; Zhang Song; Wang Rui; Hu Ying; Zhang Jing-lu; et al. (International Journal of Endocrinology)
Objective. To evaluate vitamin D status and serum parathyroid hormone (IPTH) of healthy adults living in Guiyang. Design and Participants. We conducted a cross-sectional evaluation in the General Community in Guiyang by cluster sampling method. The data was a part of 1510 participants (634 men, 876 women) aged 20–79 years median 45.2 years from November 2009 to February 2010 in Guiyang Health Measures Survey. Measurements. Aradioimmunoassay was used to measure the level of 25-hydroxyvitamin D [25(OH)D] and intact parathyroid hormone (iPTH). Results.The mean serum 25(OH)D level was (20.4 ± 9.0) ng/mL and the highest level among participants aged 40–59 years (22.8 ng/mL). The mean serum PTH level was (32.1 ± 13.7) pg/mL and the lowest level among participants aged 40–50 years (30.8 ng/mL). Serum 25(OH)D was below 50 nmol/liter in 52.3%, below 75 nmol/liter in 84.6%, and above 75 nmol/liter in 15.4% of the respondents. Secondary hyperparathyroidism was 5.4% (5.4% among men and 4.6% among women). The prevalence of secondary hyperparathyroidism increased (5.8%, 6.5%, and 7.1%, resp.) with decreasing serum 25(OH)D levels among subjects who were 30 to 20, 19.9 to 10, and <10 ng/mL, respectively. Serum 25(OH)D was inversely associated with serum PTH. Conclusions. Vitamin D insufficiency and its complication of secondary hyperparathyroidism are common.